Influence of ICT Use on Body Composition and Sedentary Death Syndrome (SeDS) Risk among University of Ilorin Sandwich Students - Dominic, Olufunmilola L.; Ibraheem, Tajudeen O.; Seidina, Iliasu Y.; Odumosu, Faatihah Niyi - (NIU Journal of Social Sciences, 2017)
The ever-increasing demand for ICT has made it a leading cause of sedentariness, which is deleterious to health and wellbeing in several ways. The study examined Influence of ICT Use on Body Composition and Sedentary Death Syndrome (SeDS) Risk among University of Ilorin sandwich students. Ex-post facto research design was adopted. The population was all University of Ilorin sandwich students registered in 2015 contact session. Simple random sampling and proportionate stratified sampling was adopted to select 426 students. Standardized instruments, which consisted of portable stadiometer, body fat/hydration monitor scale and non-elastic tape rule, were used to assess body composition. Self-reported ICT use and physical activity level were obtained using modified Global Physical Activity Questionnaire (GPAQ). Pilot test was conducted to recalibrate and ascertain functionality of the body composition instruments while the questionnaire was validated by experts and subjected to test retest for reliability. A coefficient of 0.77r was obtained as evidence of its reliability. Data were analyzed using charts, descriptive statistics of percentage, mean, and standard deviation as well as inferential statistics of Pearson Product Moment Correlation. Hypotheses were tested at statistical significance of 0.05. A significant relationship was found between ICT use and sedentariness while excessive body fat was a major indicator for SeDS among University of Ilorin sandwich students. The researchers recommended that student should habitually exercise for at least 30 minutes on 3-5 days weekly; sit less and move more daily and take 3-5 minutes of physical activity breaks after every hour of continuous ICT use. Keywords: Body Composition, Disease, Health, Physical Activity, ICT use, Sedentariness